A study on obsolescence resolution profiles - Romero Rojo, Francisco Javier; Roy, Rajkumar; Shehab, Essam; Cheruvu, Kalyan (Professional Engineering Publishing, 2012)
This paper presents a study assessing the probability of selecting a resolution approach to tackle an obsolescence issue. First, the Delphi method was applied across an industry expert panel to derive a set of 15 obsolescence resolution profiles (ORPs). The ORPs represent the probability of using each obsolescence resolution approach to tackle an obsolescence issue. Each ORP is characterized by the complexity level of the obsolete component and the level of proactiveness for obsolescence management, which have been identified as the two major factors that influence the probability of using each resolution approach. Second, the results were enhanced by means of a definitions refinement workshop. Finally, the ORPs were refined and validated by means of a workshop with experts based on the theoretical trends expected for each resolution probability. More than 40 experts in obsolescence from across the UK from the defence, aerospace, railway and nuclear sectors have participated in the study.